Intestinal obstruction due to appendicitis in a 3-month-old child - Gulan Maree; Alaa Ghuzlan; Ferhad Hemi; Ibrahem Sheikh Mohamad; Wajih Ali (Elsevier, 2022)
Appendicitis is the most common surgical abdominal emergency in children, but it is uncommon in infants. We present a 3-month-old boy with intestinal obstruction caused by appendicitis. The radiography image revealed multiple air fluid levels and dilated bowls. Appendicitis was discovered during laparotomy exploration and was surgically removed. The patient was discharged home in good health 3 days after surgery.